Dzień lasu : sobota 27 kwietnia 1946. (Gdynia : [wydawca nieznany], 1946)
Afisz z programem uroczystości.
Keywords: Opera Leśna (Sopot) -- 1945-1970.; Molo sopockie (Sopot, Polska).; Sopot (Polska) -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- źródła